PENINGKATAN KECERDASAN INTERPERSONAL MELALUI PEMBELAJARAN KOOPERATIF - Yusdiana, Yusdiana (JPUD - Jurnal Pendidikan Usia Dini, 2014)
Abstract: The objective of this research was to improve the interpersonal intelligences improve early childhood learning cooperative at Kindergarten Asy-Syifa West Java city of Serang. The data were collected through participant observation using interview, observation, document study, and recording. The data analysis and interpretation indicates that: The results obtained showed that the increase of 21,15%. In a quantitative comparison of child interpersonal intelligences before and after the action. Informant Number 13; Raw Data Pretest Total Score 858; Average Class Pretest 66; Raw Data posttest Total Score 1184; Average Class posttest 91.08. Based on these results, the researchers suggest: 1) Teachers should create a conducive learning process, comfortable and fun, setting up media which aims to improve the interpersonal intelligences concept in concrete terms so that the child can be stimulated properly, 2) schools, better prepare facilities and varied infrastructure that supports interpersonal intelligences education so as to improve social interaction, communication, socialization, empathy, and collaboration . Keywords: Interpersonal Intelligences, Cooperative Learning, Action Reacrh Abstrak: Tujuan dari penelitian ini untuk meningkatkan kecerdasan interpersonal melalui pembelajaran kooperatif di TK As-Syifa di Serang. Data yang dikumpulkan melalui observasi partisipan dengan wawancara, observasi, studi dokumentasi, dan video rekaman. Analisis data dan interpretasi menunjukkan bahwa hasil peningkatan sebesar 21,05%. Pada satu perbandingan kwantitatif dari inteligen hubungan antar pribadi anak sebelum dan setelah aksi. Angka penutur asli 13; Data mentah Pretest Jumlah Score 858; Merata-ratakan Kelas Pretest 66; Data mentah post test Jumlah Score 1184; Merata-ratakan Kelas posttest 91.08. Berlandaskan hasil ini, peneliti sarankan: (1) Guru harus menciptakan satu belajar mungkinkan berjalan, nyaman dan ceria, membuat media yang mana bertujuan meningkatkan inteligen hubungan antar pribadi anak dapat dirangsang dengan baik; (2) sekolah, persiapkan lebih baik fasilitas dan membedakan infrastruktur dukungan itu untuk mendukung kecerdasan interpersonal untuk meningkatkan interaksi sosial, komunikasi, sosialisasi, empati, dan kerjasama. Kata kunci: Kecerdasan Interpersonal, Pembelajaran Kooperatif, Penelitian Tindakan